Zinc effects on enzymes of oral bacteria - Mai Phuong, Nguyen Thi; Nghia, Phan Tuan (Academia Journal of Biology, 2014)
Zinc (Zn) is a known inhibitor of acid production by mutans streptococci. Our primary objective was to extend current knowledge of the physiologic bases for this inhibition of Zn on enzymes of oral bacteria. Zn inhibited the F-ATPase of permeabilized cells of S. mutans with a 50% inhibitory concentration of about 1 mM for cells in suspensions. Zn inhibited the phosphoenolpyruvat: sugar phosphotransferase system with 50% inhibition at about 0.3 mM ZnSO4. Zn inhibited the alkali production from arginine or urea and was a potent enzyme inhibitor for arginine deiminase of S. rattus FA-1 and urease of S. salivarius. Moreover, Zn acted mainly as a pro-oxidant for oral bacteria by inhibiting NADH oxidase, considered to be protective against oxidative stress and also other protective enzymes, which catalyzed the degradation of H2O2, including thiolperoxidase (IC50 = 0.1 mM), hypothiocyanite reductase (IC50 = 0.1 mM) and glutathione reductase (IC50 = 0.4 mM). The results have suggested that Zn had a potential use not only in oral care products, but also in different fields of medicine.